Data supporting 'Non-stationary control of the NAO on European rainfall and its implications for water resource management' - Rust, William; Holman, Ian P.; Corstanje, Ronald; Cuthbert, Mark; Bloomfield, John P. (Cranfield University, 2023)
10-year window rolling correlation between NAOI and GPCC gridded rainfall data for Western Europe. Grid cells between -13-20° Longitude and 35-70° Latitude were used to represent Western Europe.
Keywords: NAO index'; 'precipitation patterns'; 'water resource management'; 'Climate Science'; 'Water Resources Engineering'